Diffusive fractionation of noble gases in mantle with magma channels: Origin of low He/Ar in mantle-derived rocks - Yamamoto J.; Nishimura K.; Sugimoto T.; Takemura K.; Takahata N.; Sano Y. (My University, 2009)
By crushing olivine and pyroxene phenocrysts in volcanic rocks from Kyushu Island, Japan, we determined 3He/4He of 3–7 Ra and 40Ar/36Ar of up to 1750. These values are lower than those of MORB. 4He/40Ar⁎ (down to 0.1) is much lower than the production ratio of 4He/40Ar⁎ (1–5), where an asterisk denotes correction for the atmospheric contribution. Such values are typical of mantle-derived samples from the island arcs and active continental margins. Although the origin of the low 3He/4He and 40Ar/36Ar of subcontinental mantle has been widely discussed, low 4He/40Ar⁎ has been given little attention. Actually, 3He/4He and 4He/40Ar⁎ of phenocrysts overlap with those of subcontinental mantle xenoliths. Although noble gas compositions of phenocrysts are affected considerably by diffusive fractionation in ascending magma, they have little effect on the noble gases in the mantle xenoliths because it takes 100 years for He/Ar fractionation of ca. 15% for a mantle xenolith with 5 cm diameter. Therefore, the low 4He/40Ar⁎ of the mantle xenoliths is inferred to result from another kinetic fractionation in the mantle. During generation and migration of magma in the mantle, lighter noble gases diffuse rapidly out into the magma. This diffusive fractionation can explain low 4He/40Ar⁎ and somewhat low 3He/4He in the residual mantle. Furthermore, the combination of the diffusive fractionation and subsequent radiogenic ingrowth explain the fact that data from subcontinental mantle xenoliths have extremely low 3He/4He and various 4He/40Ar⁎. Consequently, 4He/40Ar⁎ and 3He/4He in mantle-derived materials are proposed as indicators of the degree of noble gas depletion of the source mantle.
Keywords: noble gases; SCLM; diffusive fractionation; magma migration; phenocryst; mantle xenolith